Peli1 Modulates the Subcellular Localization and Activity of Mdmx - Li, Dawei; Tavana, Omid; Sun, Shao-Cong; Gu, Wei (Cancer research (Chicago, Ill.), 2018)
Mdm2 and Mdmx, both major repressors of p53 in human cancers, are predominantly localized to the nucleus and cytoplasm, respectively. The mechanism by which subcellular localization of Mdmx is regulated remains unclear. In this study, we identify the E3 ligase Peli1 as a major binding partner and regulator of Mdmx in human cells. Peli1 bound Mdmx in vitro and in vivo and promoted high levels of ubiquitination of Mdmx. Peli1-mediated ubiquitination was degradation-independent, promoting cytoplasmic localization of Mdmx, which in turn resulted in p53 activation. Consistent with this, knockdown or knockout Peli1 in human cancer cells induced nuclear localization of Mdmx and suppressed p53 activity. Myc-induced tumorigenesis was accelerated in Peli1-null mice and associated with downregulation of p53 function. Clinical samples of human cutaneous melanoma had decreased Peli1 expression, which was associated with poor overall survival. Together, these results demonstrate that Peli1 acts as a critical factor for the Mdmx–p53 axis by modulating the subcellular localization and activity of Mdmx, thus revealing a novel mechanism of Mdmx deregulation in human cancers. Significance: Peli1-mediated regulation of Mdmx, a major inhibitor of p53, provides critical insight into activation of p53 function in human cancers. Cancer Res; 78(11); 2897–910. ©2018 AACR.